A funnel-type stepwise filtering strategy for identification of potential Q-markers of traditional Chinese medicine formulas - Jiang, Yuhang; Chen, Mengying; Gang, Hongchuan; Li, Xuejiao; Zhai, Chuanjia; Feng, Zhiyang; Luo, Gan; Gao, Xiaoyan (Frontiers in Pharmacology, 2023)
Quality marker (Q-marker) serves as an important driver for the standardization of the quality control of traditional Chinese medicine (TCM) formulas. However, discovering comprehensive and representative Q-markers from TCM formulas remains challenging. This study aimed to screen Q-markers of Hugan tablets (HGT), a famous TCM formula with ideal clinical effects against liver diseases. To address this problem, a funnel-type stepwise filtering strategy integrating compounds characterization, characteristic chromatogram, determination analysis, metabolic pathway and network pharmacology was proposed in this study. Firstly, the UPLC-Q-Exactive-Orbitrap/MS was applied to comprehensively identify the chemical compositions of HGT and single herbs. The specific components of each herb in the HGT formula were then clarified by integrating HPLC characteristic chromatogram and biosynthesis pathway analysis of different medicinal materials. Subsequently, the content of specific components was determined based on the “measurability” of the Q-markers, which clarified the specific components that can be quantified in single drugs of HGT. Furthermore, the metabolism of the above components in rats was studied to reveal their forms in vivo, and further was used for network pharmacology research to screen out potential active components. At last, according to corresponding metabolic rules, the prototype components with therapeutic effects in HGT were traced and preliminarily chosen as Q-markers. As a result, 128 chemical compounds were identified in HGT and different herbs, and 11 specific components were screened. Then, the content of specific components in 15 batches of HGT was determined, confirming their measurability. After that, 26 xenobiotics (11 specific components and 15 metabolites) were detected in rats. Furthermore, 14 potential active ingredients were selected from the “TCM formula-single herbs-compounds-targets-pathways” network. Finally, in combination with the metabolic pathways of different components, 9 prototype components of HGT formula were defined as comprehensive and representative Q-markers. Our study not only provided a scientific basis for the improvement and secondary development of the quality standard of HGT, but also proposed a reference method for discovering and identifying Q-markers of TCM preparations.